The second highest chromosome count among vertebrates is observed in cultured sturgeon and is associated with genome plasticity. Issue 1 (December 2016) - Havelka, Miloš; Bytyutskyy, Dmytro; Symonová, Radka; Ráb, Petr; Flajšhans, Martin
Abstract Background One of the five basal actinopterygian lineages, the Chondrostei, including sturgeon, shovelnose, and paddlefish (Order Acipenseriformes) show extraordinary ploidy diversity associated with three rounds of lineage-specific whole-genome duplication, resulting in three levels of ploidy in sturgeon. Recently, incidence of spontaneous polyploidization has been reported among cultured sturgeon and it could have serious negative implications for the economics of sturgeon farming. We report the occurrence of seven spontaneous heptaploid (7n) Siberian sturgeonAcipenser baerii, which is a functional tetraploid species (4n) with ~245 chromosomes. Our aims were to assess ploidy level and chromosome number of the analysed specimens and to identify the possible mechanism that underlies the occurrence of spontaneous additional chromosome sets in their genome. Results Among 150 specimens resulting from the mating of a tetraploid (4n)A. baerii (~245 chromosomes) dam with a hexaploid (6n)A. baerii (~368 chromosomes) sire, 143 displayed a relative DNA content that corresponds to pentaploidy (5n) with an absolute DNA content of 8.98 ± 0.03 pg DNA per nucleus and nuclear area of 35.3 ± 4.3 μm2 and seven specimens exhibited a relative DNA content that corresponds to heptaploidy (7n), with an absolute DNA content of 15.02 ± 0.04 pg DNA per nucleus and nuclear area of 48.4 ± 5.1 μm2 . Chromosome analyses confirmed a modal number of ~437 chromosomes in these heptaploid (7n) individuals. DNA genotyping of eight microsatellite loci followed by parental assignment confirmed spontaneous duplication of the maternal chromosome sets via retention of the second polar body in meiosis II as the mechanism for the formation of this unusual chromosome number and ploidy level in a functional tetraploidA. baerii . Conclusions We report the second highest chromosome count among vertebrates in cultured sturgeon (~437) after the schizothoracine cyprinidPtychobarbus dipogon with ~446 chromosomes. The finding also represents the highest documented chromosome count in Acipenseriformes, and the first report of a functional heptaploid (7n) genome composition in sturgeon. To our knowledge, this study provides the first clear evidence of a maternal origin for spontaneous polyploidization in culturedA. baerii . To date, all available data indicate that spontaneous polyploidization occurs frequently among cultured sturgeons.